The Game-Changing Impact of AI Chatbots on Education ChatGPT and Beyond - Vasudevan, Asokan; Vorfi Lama, Alma; Sain, Zohaib Hassan (Ali Institute or Research and Publication, 2024)
ChatGPT, an AI-driven chatbot, delivers coherent and valuable responses by analysing extensive data sets. This article explores the profound impact of ChatGPT on contemporary education, as discussed by prominent academics, scientists, distinguished researchers, and engineers. The study delves into ChatGPT's capabilities, its application in the education sector, and the identification of potential concerns and challenges. Initial assessments reveal variations in ChatGPT's performance across diverse subjects, including finance, coding, mathematics, and general public queries. While ChatGPT can assist educators by generating instructional content, providing suggestions, serving as an online educator for learners, answering questions and revolutionising education through smartphones and IoT devices, it has shortcomings. These include the risk of generating inaccurate or false information and evading plagiarism detection systems, a critical concern for maintaining originality. The commonly reported